Investigation of the gradation effect on ballast mechanical behaviors by means of discrete element modeling - part 1. (October 2019) - Wang, B; Martin, U; Rapp, S; Schuk, V
Abstract: The ballast gradation has a strong influence on the mechanical behavior of ballast aggregates. Discrete Element Method (DEM) based simulations are performed to investigate the gradation effect of ballast aggregates on their settlement, ballast position rearrangement, breakage rate and void ratio. This is the first part of two papers. In this article, a newly developed ballast random form generator is described. With this generator five form databases of different ballast gradations are established. A box test and its corresponding DEM simulation are usually performed to calibrate and to investigate the mechanical behavior of small-scaled ballast aggregates with different gradations. The ballast stones are simulated by the Bonded Particle Models with the Flat Joint contact model to enable the investigation of the breakage behavior of each ballast stone.